The Role of Moral and Psychological Atmosphere of Universities in Shaping the Personality of the Modern Student - Pimenova, Olha (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The paper analyzes the impact of the moral and psychological atmosphere of the university on formation of the personal qualities of future professionals, in particular their personal freedom. The author provides own definition of "moral psychological atmosphere" based on the results of quantitative and qualitative sociological research focuses on such a component of the university moral and psychological atmosphere like the style of the relationship between the main actors of the educational process in high school - students, teachers, university administration. It is stressed that more favorable conditions for the formation of personal freedom of modern students are in universities which activity if is inherented by culture of freedom, which means absence of certain coercive sanctions towards the personality of the future specialist.